Saúde ambiental na Atenção Primária no município de Belo Horizonte - Daniela de Almeida Ochoa Cruz (2018)
Primary environmental care comprises a type of environmental strategy that is essentially preventive and participatory, operating in a local dimension that discerns the prerogative of people to live in a healthy and appropriate context, with the right to be informed about the risks health, well-being and survival. Primary environmental care also refers to responsibilities and duties in the protection, maintenance and recovery of health and the environment (PAHO, 1999). The present cross-sectional, quantitative-qualitative study of the Belo Horizonte Municipal Health System aims to analyze the environmental health actions in the Primary Health Care of the municipality, to describe what are the actions effectively developed and to identify how managers, professionals and users perceive the environmental health in its reference territory of Primary Health Care. The work in question is linked to the project entitled "Health Promotion and Prevention of Violence in Primary Health Care", whose instruments of data collection were developed in previous years for other municipalities. These were changed, questions being withdrawn and others added, according to the need and characteristics of the municipality where it would be applied. The sociodemographic information of the two instruments was used, as well as a questionnaire from the professional and the user form, as well as more information about water courses and development of environmental actions, as well as a third instrument developed by the author for the manager's application and with 31 issues. It was noticed that users, health professionals, central and district level managers, and basic unit managers are mostly not aware of or do not carry out environmental health actions in the area of primary care reference coverage. In addition, most of them are also unaware of the situation of the streams in the area or the name of the river basin to which such water courses are a part. The environmental theme still needs to be addressed, through the insertion of topics in the training courses, courses provided by the work, information by the media, among other means, since the data show that less than half of this public has knowledge or develop actions of health, in their area of residence or work. The theme is not yet valued by the community and health professionals and this approach is necessary to guarantee improvement of the health of the population and the environment where they live and / or work. After the data of the study, it was realized that working with the territorial unit of watershed comprises a challenge for the health sector, but at the same time, essential for the advancement of the work process of the professionals. The team needs to discover the waterways. In addition, it is believed to be of fundamental importance the creation of a municipal environmental health policy with guidelines to be followed by environmental health surveillance professionals, articulating their actions with primary health care professionals in line with the concept of Primary Environmental Care, created by PAHO in 1999 and by the document "Subsidies for the Construction of the National Environmental Health Policy" of 2007 developed by the Ministry of Health.